Integrasi IoT pada Mesin Roasting Kopi Fluidized Bed - Wijaya Kusuma; Rahman Azis Prasojo; Ibrahim; Lukman Hakim; Muhammad Arief Furqon; Mochammad Erfian Ramadhan (Politeknik Negeri Malang, 2025)
This research presents the development of an electric coffee roasting machine using the fluidized bed method, integrated with an Internet of Things (IoT)-based monitoring and control system. The system was designed to address limitations of previous prototypes that lacked remote temperature monitoring and automation. The roasting chamber utilizes a hot air stream to create fluidization, enabling uniform bean agitation and heat distribution. Key hardware includes a thermocouple sensor (MAX6675), an ESP32-S3 microcontroller, an AC light dimmer for heater control, and an electronic speed controller (ESC) for blower regulation. A user interface is provided via a TFT LCD screen and a custom mobile application connected through Firebase Realtime Database. Roasting profiles—consisting of bean type, target roast level, and batch weight—can be selected and executed automatically. The system was tested with various bean weights (50–250 g), demonstrating accurate temperature control, stable fluidization, and consistent roast levels. Results showed a temperature deviation below ±1°C from reference measurements, and all tests produced medium roast coffee with uniform color and aroma. The integration of IoT improves usability, process reliability, and potential scalability for small-scale roasting operations.